2013
DOI: 10.1159/000345203
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Susceptibility to Variant Creutzfeldt-Jakob Disease

Abstract: The emergence of bovine spongiform encephalopathy (BSE) in cattle and, subsequently, its transmission to humans resulting in variant Creutzfeldt-Jakob disease (vCJD) in the UK has proved to be one of the major public health scares of the century. The oral route of infection, the long incubation period, and the incredible resistance of the transmissible infectious agent to various forms of decontamination poses unique challenges. Fortunately, despite extensive exposure of the UK population to contaminated meat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The elk PRNP codon 132 polymorphism is homologous to the human PRNP codon 129 polymorphism that encodes either methionine (M) or valine (V) [ 39 , 40 ]. In TSE-affected humans, the MM129 genotype is associated with susceptibility to kuru [ 23 ] and variant Creutzfeldt-Jakob disease (vCJD) [ 38 ]. Some studies have found that elk expressing prion protein homozygous for methionine at codon 132 (hereafter referred to as MM132 elk) are over-represented among CWD-affected elk [ 11 , 12 , 31 , 41 ], while another study concluded that elk of all 3 genotypes (MM132, LM132, LL132) show equivalent susceptibility [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The elk PRNP codon 132 polymorphism is homologous to the human PRNP codon 129 polymorphism that encodes either methionine (M) or valine (V) [ 39 , 40 ]. In TSE-affected humans, the MM129 genotype is associated with susceptibility to kuru [ 23 ] and variant Creutzfeldt-Jakob disease (vCJD) [ 38 ]. Some studies have found that elk expressing prion protein homozygous for methionine at codon 132 (hereafter referred to as MM132 elk) are over-represented among CWD-affected elk [ 11 , 12 , 31 , 41 ], while another study concluded that elk of all 3 genotypes (MM132, LM132, LL132) show equivalent susceptibility [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is not yet possible to rule out that the incidence of vCJD may increase again, particularly if different genetic subgroups with longer incubation periods exist. Work in transgenic mice expressing human PrP has demonstrated that all codon 129 genotypes are potentially susceptible to infection with BSE, albeit with different incubation periods (Asante et al., ; Cassard et al., ; Padilla et al., ; Saba & Booth, ).…”
Section: Zoonotic Aspects and Socio‐economic Impactmentioning
confidence: 99%
“…It is not yet possible to rule out that the incidence of vCJD may increase again, particularly if different genetic subgroups with longer incubation periods exist. Work in transgenic mice expressing human PrP has demonstrated that all codon 129 genotypes are potentially susceptible to infection with BSE, albeit with different incubation periods(Asante et al, 2002;Cassard et al, 2014;Padilla et al, 2011;Saba & Booth, 2013).Non-human primates and transgenic mouse models expressing human PrP have been shown to be permissive to infection with both C-BSE and L-BSE(Beringue et al, 2008;Kong et al, 2008; Mestre- Frances et al, 2012) although not, to date, with H-BSE, suggesting…”
mentioning
confidence: 99%
“…More specifically, this singlenucleotide polymorphism (SNP) rs1799990 at codon 129 of the PRNP gene encodes for either methionine (M = ATG) or valine (V = GTG) and is a known genetic factor that contributes to the risk of developing vCJD. 30,38 In cattle, the western blot profile of C-BSE differs from that of atypical BSE. Atypical BSE cases are designated as such due to the observable variation in molecular mass profiles.…”
Section: Prion Disease Strainsmentioning
confidence: 99%